2014
DOI: 10.1074/jbc.m114.577692
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Pentose Phosphate Pathway and Gluconeogenesis from Glycerol in the Liver

Abstract: Background: Hepatic pentose phosphate pathway activity is difficult to monitor in vivo. Results: Hepatic pentose phosphate pathway results in different ratios of doubly labeled glucose isotopomers after administration of [U-13 C 3 ]glycerol. Conclusion: [1,2-13 C 2 ]glucose produced by the hepatic pentose phosphate pathway is quantified. Significance: A simple method is presented to detect the activity of hepatic pentose phosphate pathway in vivo from analysis of plasma glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 21 publications
3
59
0
Order By: Relevance
“…We also showed that viscerally obese individuals had a trend toward lower 13 C-labeled glucose isotopomers produced through the PPP or TCA cycle suggesting a possible link between excess VAT, inflammation, PPP dysregulation, and mitochondrial failure. Furthermore, we observed that refeeding results in lower 13 C enrichment in glucose through direct gluconeogenesis from [U- 13 C 3 ] glycerol, through PPP activity or through the TCA cycle prior to gluconeogenesis, compared with the fasting state, consistent with prior observations in non-obese refed rodents [17]. Overall, our findings provide intriguing evidence that excess VAT may act as a “constitutively fed state” and result in increased risk for hyperglycemia and type 2 diabetes through overstimulation of hepatic gluconeogenesis by chronic delivery of glycerol arising from mesenteric triglyceride turnover directly into the portal circulation and to the liver.…”
Section: 0 Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also showed that viscerally obese individuals had a trend toward lower 13 C-labeled glucose isotopomers produced through the PPP or TCA cycle suggesting a possible link between excess VAT, inflammation, PPP dysregulation, and mitochondrial failure. Furthermore, we observed that refeeding results in lower 13 C enrichment in glucose through direct gluconeogenesis from [U- 13 C 3 ] glycerol, through PPP activity or through the TCA cycle prior to gluconeogenesis, compared with the fasting state, consistent with prior observations in non-obese refed rodents [17]. Overall, our findings provide intriguing evidence that excess VAT may act as a “constitutively fed state” and result in increased risk for hyperglycemia and type 2 diabetes through overstimulation of hepatic gluconeogenesis by chronic delivery of glycerol arising from mesenteric triglyceride turnover directly into the portal circulation and to the liver.…”
Section: 0 Discussionsupporting
confidence: 90%
“…Total 13 C enrichment in plasma glucose is measured by the sum of all glucose isotopomers with excess 13 C. Additional information about specific pathways is derived from specific glucose isotopomers [17, 18]. Initially, glycerol is phosphorylated in the liver by glycerol kinase and is converted to DHAP and GA3P.…”
Section: 0 Theory/calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of hepatic PPP activity is based on the principle that the 13 C-labeling patterns in the "top" or "bottom" half of glucose carbons reflect the triose pool and that the relative concentrations of double-labeled trioses cannot be altered by transaldolase activity or incomplete equilibration at the level of triose phosphate isomerase (15). Transaldolase activity exchanges fructose 6-phosphate carbons 4 -6 with GA3P carbons.…”
Section: Methodsmentioning
confidence: 99%
“…Recently methods were introduced to study hepatic PPP by analysis of plasma glucose and hepatic fatty acid esterification in rodents receiving intragastric 13 C-labeled glycerol (15,16). After the administration of [U- 13 C 3 ]glycerol, different metabolic pathways in the liver generate unique 13 C-labeling patterns in the products of hepatic biosynthesis, glucose and TAGs, that are exported into circulation and readily sampled in venous blood.…”
mentioning
confidence: 99%